2016
DOI: 10.1016/j.euprot.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the tumor microenvironment proteome in prostate cancer using laser capture microdissection coupled to LC⿿MS⿿A technical report

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…Thus we consider them a satisfactory model for development of CRPC. Our group has previously applied workflows similar to those described here for proteomic profiling of the PCa tumour microenvironment using laser capture microdissected regions of patient tumour tissue [57]. Reassuringly, there is significant overlap between changing proteins identified in this cell-based study and previous tissue-based studies (data not shown), thus providing confidence that our cell line system represents a faithful model of the in vivo tumour microenvironment.…”
Section: Discussionsupporting
confidence: 52%
“…Thus we consider them a satisfactory model for development of CRPC. Our group has previously applied workflows similar to those described here for proteomic profiling of the PCa tumour microenvironment using laser capture microdissected regions of patient tumour tissue [57]. Reassuringly, there is significant overlap between changing proteins identified in this cell-based study and previous tissue-based studies (data not shown), thus providing confidence that our cell line system represents a faithful model of the in vivo tumour microenvironment.…”
Section: Discussionsupporting
confidence: 52%
“…We do, however recognize that accurately epotimizing the in vivo tumour microenvironment in a 2D cell culture system is effectively impossible. The Previously, we have applied workflows similar to those described here for proteomic profiling of the PCa tumour microenvironment using laser capture microdissected regions of patient tumour tissue [ 66 ]. Reassuringly, there is significant overlap between changing proteins identified in this cell-based study and previous tissue-based studies (data not shown), thus providing confidence that our cell line system represents a faithful model of the in vivo tumour microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…This technique holds an immense potential given the multitude of downstream analyses that can follow (genotypic/transcriptomic profiling, signaling pathways discoveries, biomarker identification, and others; Espina et al, 2006 ). When it comes to PCa, LCM has been employed in a multitude of studies and several protocols have been established to generate downstream analyses ( Lugli et al, 2015 ; Staunton et al, 2016 ). For instance, using LCM on N-cadherin positive patient-derived subpopulations of cells, Kolijn et al (2018) demonstrated that during EMT, indoleamine 2,3-dioxygenase is overexpressed.…”
Section: Laser-capture Microdissection and Single-cell Rna-sequencingmentioning
confidence: 99%